"Home and beautiful things": Aspirational politics in dance bars in India. (June 2017) - Lakkimsetti, Chaitanya
This article examines the controversy surrounding women's sexual labor of dancing in the city of Mumbai in the western state of Maharashtra, India. Whereas much of the debate around the dance bars focuses on bar dancers' livelihood and right to work, I turn the discussion to the realm of desire and consumption to show how intimate labor is connected to class aspirations. Using legal, media and cultural sources, I suggest that the intimate labor in dance bars produces new aspirations for bar dancers. These aspirations are made possible by the specific labor and exchange conditions and relational possibilities that are specific to the bars, illustrating what I call the aspirational politics of sex, where sexual labor acts as a site for individual existential pursuits such as social mobility and a sense of well-being. Dance bars offer young women from marginalized communities the opportunity for livelihood and social mobility as well as access to middle-class lifestyles through involvement in new consumer cultures but without the corresponding status or protection of being middle class. Additionally, by analyzing the politics around the ban on dancing in Mumbai, the article reveals the cultural conflicts inherent in sexual labor and illuminates an important arena where women can mobilize hegemonic discourses to serve their own interests and stretch the limits of their subordination.